Flux decline study of tubular ceramic and flat sheet UF membranes in textile wastewater treatment - Zebić Avdičević, Maja (Array, 2019)
This work gives an assessment of the application of two ultrafiltration membrane types, which are the same in pore size but different in chemistry and configuration module, for textile wastewater treatment. Characterization was based on the solute rejection data of two commercial membranes, flat sheet polyethersulfone (PES) and tubular multichannel ceramic membrane, and flux decline was provided using polyethylene glycol (PEG) solutions of different molar mass. The permeate flux recovery after chemical cleaning was evaluated, and the efficiency of wastewater treatment was estimated on the basis of the analysis of textile wastewater and permeate. The permeate flux decline study showed that fouling was less likely to occur when PES membrane was used for wastewater treatment. PES flat membrane has proven to be more effective in the treatment of wastewater with total organic carbon (TOC) and colour removal efficiency of 72 % and 85 % respectively.